States, Banks, and the Financing of the Economy: Fiscal Policy and Sovereign Risk Perspectives - Morten Balling; Peter Egger; Ernest Gnan; Axel A. Weber; Harald W. Stieber; Stavros Vourloumis; António Afonso; Jo\~ao Tovar Jalles; Franco Bruni; André van Poeck; Maartje Wijffelaars; Séverine Menguy; et al. (SUERF - The European Money and Finance Forum, 2013)
On 5-6 September 2012 SUERF held its 30th Colloquium “States, Banks, and the Financing of the Economy” at the University of Zürich, Switzerland. The papers included in this SUERF Study are based on contributions to the Colloquium. All the chapters in this publication discuss from different angles the complex interrelations between states and financial systems, which have developed in recent years with economic, financial and sovereign debt crises. While the contributions included here primarily look at fiscal policy and sovereign risk perspectives, papers on the monetary policy and regulatory perspectives, which were also dealt with at the Zürich Colloquium, will be published in SUERF Study 2012/3 “States, Banks, and the Financing of the Economy: Monetary Policy and Regulatory Perspectives”.
Keywords: C23; E43; E62; F33; F5; G1; G12; G15; G21; G28; G33; H1; H50; H63; H7; 330; bank resolution; Banking Crises; bond market fragmentation; budget decomposition; budget deficit; corporate bonds; credit supply; crisis; Cross-border banking; Debt Sustainability; Economic and Monetary Union; Economic governance; Economic Governance Six-Pack; Enhanced cooperation; Eurobonds; European Semester; Financial markets; financial stability; Fiscal Compact; Fiscal Policy Coordination; Government interventions; Interest rate; Italy; panel analysis; panel causality; Political integration; Public debt; Recession; Sovereign debt; Stability and Growth Pact; Schuldenkrise; Länderrisiko; Eurozone; Bankenregulierung; EU-Staaten